Contextualizing policy mixes : A configurational study on rapid transitions - Juntunen, Jouni K.; Shakeel, Shah Rukh (Elsevier, 2025)
The policy mixes in sustainability transitions have been recognized as a central component in accelerating decarbonization. Policy mixes are embedded in a broader institutional and structural order involving technologies, infrastructures, markets, practices, and environmental conditions within socio-technical transitions. In this paper, we examine how various combinations of demand-pull policy mixes, and infrastructural, environmental, and market configurations result in either rapid or slow transitions. We draw on European heat pump diffusion as a novel innovation featuring very different diffusion levels within the continent. The analysis draws on a country-level data set of 20 European countries, and a configurational analysis using the fuzzy-set Qualitative Comparative Analysis (fsQCA) method. The policy mix measures for configurational analysis are constructed using data on sector specific policy instruments, taking in economic policies, regulatory policies, and mandatory and voluntary soft and systemic instruments. We complement the model with environmental conditions, infrastructure data on gas and heating networks, and market conditions. Three key findings emerged. First, we contextualize policy mixes to reveal how various configurations can lead to either rapid or slow transitions. Second, we contribute to the research on energy transitions by demonstrating the importance of infrastructural arrangements. Third, we make a methodological contribution by exemplifying how the two-step comparative case study method can separate slowly changing remote conditions and more rapidly evolving proximate conditions in studies on sustainability transitions. The results emphasize system-level environment and climate policy approaches that improve the cost competitiveness of clean technologies.
Keywords: Policy mix; Green innovation diffusion; Socio-technical transitions; Institutional complexity; Configurational analysis; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; fi=Markkinointi|en=Marketing|